Designing and conducting cost-effectiveness analysis studies in healthcare - Ismail, Noor Haslinda; Juni, Muhamad Hanafiah; Abdul Manaf, Rosliza; Ibrahim, Faisal (Community Health Society Malaysia (CHSM), 2017)
Background: Health economic evaluation is essentials in the era of growing development of new health interventions to improve health of people and healthcare system. It focuses on the comparative analysis of alternative options in terms of both costs and consequences. Economic evaluation using cost-effectiveness analysis (CEA) technique helps the analyst to identify the most cost-effective option for achieving a pre-set objective. It is a method of assessing whether the current mix of interventions is efficient as well as whether a proposed new technology or intervention is appropriate. This article aims to describe the essentials steps in designing and conducting health economic evaluation studies in healthcare settings using CEA technique.